The Importance of Context in Moral Judgments. (March 2020) - Schein, Chelsea
There is a gap between morality as experienced and morality as studied. In our personal and professional lives, moral judgments are embedded within a specific context. We know the who, what, where, and when and often can infer the why; we know the broader context of actions; and we may have a specific relationship with the actors. However, scholarly theorizing is often built on inferences from participants' responses to decontextualized, impoverished stimuli. In our quest for uncovering general psychological truths, moral psychologists have examined evaluations of poorly guarded trolleys, strangers with odd sexual proclivities, and endorsement of abstract principles. The four articles included in this section demonstrate the power of contextualizing morality. In the current article, I place these papers within a broader framework for how scholars can contextualize morality research. I then argue why contextualizing morality matters: not only do contextualized questions better reflect the nuances of reality but also contextualized judgments might be key for improving predictions of moral behavior and understanding moral change.